Legal Consequences of Establishing a Limited Liability Company by a Foundation in Violation of the Law - Hatimah, Khusnul; Sulistiyono, Adi; Sudarwanto, Al Sentot (International Journal of Law and Society, 2023)
The purpose of this research is to analyze the responsibility of a notary and the legal consequences for a limited liability company that a foundation has established but violates the law on foundations. The research was conducted using doctrinal legal research methods. The results of the study show that: (1) Notaries as officials who are authorized in terms of doing authentic deeds, including the deed of establishment of limited liability companies established by foundations, have a great responsibility insofar as they concern the formal requirements of authenticating the deed. However, the notary is not responsible for the substance of the deed because it is the will of the parties themselves, so if what is violated is the formal terms of the deed, the notary can be sued for compensation and fines. (2) The legal consequence for the limited liability company is that it violates Article 7 of the Law on Foundations. It is null and void because the deed of an establishment violates the objective requirements of the legal terms of an agreement regulated in Article 1320 of the Civil Code. In addition, the legal status of a Limited Liability Company has been deemed to have never existed, causing all actions that have been carried out or carried out by the organs of the company to have no legal standing.